1993
DOI: 10.1073/pnas.90.7.2774
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of rejection induced by tumor cell-targeted gene transfer of interleukin 2, interleukin 4, interleukin 7, tumor necrosis factor, or interferon gamma.

Abstract: Interleukin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
132
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(143 citation statements)
references
References 32 publications
9
132
2
Order By: Relevance
“…The demonstration that the ACN/IFN-g cells produced NO strongly supported its role in driving the apoptotic signal to the endothelial cells. In this view, it is conceivable that a non-species-specific mediator, like NO, was responsible for inhibition of angiogenesis observed in other human IFN-transfected tumour cells growing in athymic mice (Hock et al, 1993;Fathallah-Shaykh et al, 2000;Ozawa et al, 2001;Izawa et al, 2002;Qin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration that the ACN/IFN-g cells produced NO strongly supported its role in driving the apoptotic signal to the endothelial cells. In this view, it is conceivable that a non-species-specific mediator, like NO, was responsible for inhibition of angiogenesis observed in other human IFN-transfected tumour cells growing in athymic mice (Hock et al, 1993;Fathallah-Shaykh et al, 2000;Ozawa et al, 2001;Izawa et al, 2002;Qin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…T, B and NK cells) and NIH III mice (also deficient of T, B and NK cells) (24). Nonetheless, a long latency (about 30 days) existed before tumor nodule became palpable in these immuno-compromised mice.…”
Section: The Mechanism Of Exogenous Il-4-induced Tumor Rejectionmentioning
confidence: 99%
“…In immuno-competent mice, no tumor grew out. Cell depletion study indicated that CD8 + T lymphocyte were important, whereas CD4 + T cells played only a marginal role (24). At present, a biphasic mechanism is considered to be operating for exogenous IL-4-induced tumor rejection during which a rapid, innate immune cell dominant inflammatory response inhibited tumor burden, whereby allowing T cells to be activated and to finally complete tumor rejection (Figure 1).…”
Section: The Mechanism Of Exogenous Il-4-induced Tumor Rejectionmentioning
confidence: 99%
“…In vitro, IL-7 is used to support APCinduced T-cell priming with a higher specificity than in the presence of IL-2 (Kos and Millbacher, 1992;Celis et al, 1994). Compared with other cytokines, anti-tumour response induced by paracrine-secreted IL-7 seems to be more strictly dependent on T cells (Hock et al, 1993;Miller et al, 1993), although IL-7 is able to induce LAK activity (Alderson et al, 1990;Bohm et al, 1994), to enhance NK activity (24) and to generate tumoricidal activity in monocytes (Alderson et al, 1991). In a comparative study in a mouse tumour model using a murine plasmocytoma cell line, the IL-7-secreting gene-modified tumour cells showed, in contrast to other cytokine-secreting tumour cells, a dependency of CD4+ T cells on early tumour rejection, whereas CD8+ T cells were required for long-term tumour eradication (Hock et al, 1993).…”
mentioning
confidence: 93%